Race and Reproduction in Cuba - Lucero, Bonnie A. (Book collections on Project MUSE., 2022)
"From its inception, Cuba was defined by fundamental demographic conflict. Imperial authorities envisioned the island as a white Hispanic colony. Yet, the demographic realities of colonial life proved more complex than colonial settlement projects anticipated. Race and Reproduction centers women and their reproductive labors in Cuba's historic politics of population to how the twin demographic goals of white population growth and non-white population management shaped women's reproduction from the onset of colonization through the early years of the Cuban Revolution. More than just the flows of people arriving on the island, biological reproduction-including conception, pregnancy, childbirth, breastfeeding, and other physical acts of motherhood-also played a critical role in the evolution and management of Cuba's population. In addition to contributing genetically, elite men also intervened in women's reproduction in racially specific ways. But the principal protagonists of these actions were women and the main sites of contestation were their bodies. This disconnect between policy and reality meant that interventions in women's reproductive lives did not always advance the overarching demographic goals of the colonial regime. Sustaining racial difference in the treatment of women and their infants conflicted, in many cases, with overarching demographic projects"--